Effect of terminal 3′-hydroxymethyl modification of an RNA primer on nonenzymatic primer extension. Issue 80 (12th September 2016) - Pal, Ayan; Das, Rajat S.; Zhang, Weicheng; Lang, Megan; McLaughlin, Larry W.; Szostak, Jack W.
Abstract : Displacing the hydroxyl nucleophile at the 3′-end of a primer by a single methylene group drastically decreases the rate of primer extension, illustrating the importance of the precise position of the hydroxyl nucleophile. Abstract : The significance of the precise position of the hydroxyl at the 3′-end of an RNA primer for nonenzymatic template-directed primer extension is not well understood. We show that an RNA primer terminating in 3′-hydroxymethyl-2′, 3′-dideoxy-guanosine has greatly diminished activity, suggesting that the spatial preorganization of the terminal sugar contributes significantly to the efficiency of primer extension.